Growth, Industrial Structure, and Carbon Emissions in ASEAN: A Panel Data Analysis - Gunarto, Toto; Hadiyati, Sri; Hudani, M Mufti; Ciptawaty, Ukhti; Afif, Fadeli Yusuf (Universitas Pasundan, 2025)
This study examines the relationship between economic growth, industrial growth, and carbon dioxide emissions in ASEAN countries over the period 2010–2020, with particular emphasis on the interaction between economic expansion and industrial structure. Using balanced panel data from nine ASEAN economies and employing panel regression techniques, the analysis evaluates both the direct and conditional effects of growth on environmental outcomes. The results indicate that economic growth and industrial growth each have a positive and statistically significant impact on carbon emissions. More importantly, the interaction term between economic growth and industrial growth is also positive and significant, suggesting that the environmental impact of GDP growth is amplified in economies experiencing stronger industrial expansion. These findings imply that economic growth in ASEAN remains closely linked to energy-intensive industrial activities, limiting progress toward emissions reduction. By explicitly modeling the interaction between growth and industrial structure, this study contributes to the environmental economics literature by providing a more nuanced understanding of the growth–emissions nexus in developing regional contexts.